2018
DOI: 10.1007/s00330-017-5223-z
|View full text |Cite
|
Sign up to set email alerts
|

Integrated prediction of lesion-specific ischaemia from quantitative coronary CT angiography using machine learning: a multicentre study

Abstract: • Integrated ischaemia risk score improved prediction of ischaemia over quantitative plaque measures • Integrated ischaemia risk score showed higher prediction of ischaemia than standard approach • Contrast density difference had the highest information gain to identify lesion-specific ischaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
91
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(92 citation statements)
references
References 47 publications
1
91
0
Order By: Relevance
“…Thus, compared to stenosis severity alone, diagnosis of ischemia improved with the addition of coronary plaque features and FFR derived from CCTA. These two findings were in line with observations from other cohorts [13, 14]. As a consequence, CCTA with its ability to fully quantify coronary atherosclerosis—i.e., not only coronary plaque but also the vessel wall to assess positive remodeling and the lumen to assess luminal narrowing—could refine the diagnosis of myocardial ischemia and the selection of patients for ICA with subsequent revascularization (Fig.…”
Section: Coronary Cta To Detect Hemodynamically Significant Atherosclsupporting
confidence: 90%
“…Thus, compared to stenosis severity alone, diagnosis of ischemia improved with the addition of coronary plaque features and FFR derived from CCTA. These two findings were in line with observations from other cohorts [13, 14]. As a consequence, CCTA with its ability to fully quantify coronary atherosclerosis—i.e., not only coronary plaque but also the vessel wall to assess positive remodeling and the lumen to assess luminal narrowing—could refine the diagnosis of myocardial ischemia and the selection of patients for ICA with subsequent revascularization (Fig.…”
Section: Coronary Cta To Detect Hemodynamically Significant Atherosclsupporting
confidence: 90%
“…43,44 Another potential utility of coronary CTA is to predict ischemia by assessing plaque stenosis, morphology and/or volume. [52][53][54][55][56] have revealed that increased prevalence of high-risk plaque features was associated with ischemia, especially when positive remodeling and low attenuation plaque were present. 52 Diaz-Zamudio et al has investigated if plaque characteristics assessed by quantitative CT software can predict ischemia and found that total, non-calcified and low attenuation plaque burden were associated with ischemia.…”
Section: Intra-/inter-reader Variability Of Plaque Imaging By Coronarmentioning
confidence: 99%
“…Finally, Dey and colleagues have reported on the utility of ML and boosted ensembles for the detection of plaque-specific ischemia through CCTA (AUC = 0.84) using invasive FFR as reference (Dey et al, 2018). Their report concentrated on the integration of plaque features and their integration into a strong classifying score, an advantage offered by iterative ML algorithms.…”
Section: Cardiovascular Diagnosismentioning
confidence: 99%